Difference between deoxyribose- and tetrahydrofuran-type abasic sites in the in vivo mutagenic responses in yeast - Otsuka, Chie (Oxford University Press, 2002)
We have analyzed the mutagenic specificity of an abasic site in DNA using the yeast oligonucleotide transformation assay. Oligonucleotides containing an abasic site or its analog were introduced into B7528 or its derivatives, and nucleotide incorporation opposite abasic sites was analyzed. Cytosine was most frequently incorporated opposite a natural abasic site (O) (‘C-rule’), followed by thymine. Deletion of REV1 decreased the transformation efficiency and the incorporation of cytosine nearly to a background level. In contrast, deletion of RAD30 did not affect them. We compared the mutagenic specificity with that of a tetrahydrofuran abasic site (F), an abasic analog used widely. Its mutation spectrum was clearly different from that of O. Adenine, not cytosine, was most favorably incorporated. However, deletion of REV1 decreased the transformation efficiency with F-containing oligonucleotide as in the case of O. These results suggest that the bypass mechanism of F is different from that of O, although the bypasses in both cases are dependent on REV1. We also found that the mutagenic specificity of F can be affected by not only the adjacent bases, but also a base located two positions away from F.